The Carbonization of Pomelo and Banana Peels as Adsorbent in Heavy Metal Treatment of Groundwater - Mohd Yusof, Nur Akmalzatul Syazana; Ahmad Nazri, Mohd Ariff (Recent Trends in Civil Engineering and Built Environment, 2022)
The groundwater exploitation could increase the surface water supplies due to its convenient and accessibility. However, the presence of the heavy metals are among the major contaminants of groundwater sources and would be harmful and unsafe to be used if not treated well. The contamination of heavy metal concentration may occur in the groundwater causing by various anthropogenic activities such as agricultural and industrial in the surrounding area. Therefore, this study aims to identify the properties of the groundwater in Universiti Tun Hussein Onn Malaysia (UTHM) related to its heavy metal parameter and focusing on reducing the concentration by using carbonization method on preparing pomelo and banana peels as adsorbent. The heavy metal substances that were tested are iron (Fe), aluminium (Al), zinc (Zn) and manganese (Mn). The parameters in the groundwater shall meet the requirement according to the National Guidelines for Raw Drinking Water.The adsorption process of the pomelo and banana peels signify the effectiveness in reducing the heavy metal concentration in the groundwater. The initial concentration of Fe, Al, Zn and Mn is 4.560 mg/L, 0.970 mg/L, 0.216 mg/L and 1.550 mg/L respectively. After treated using carbonized pomelo peels, the concentration of Fe, Al, Zn and Mn were reduced to 3.470 mg/L, 0.473mg/L, 0.214 mg/L and 0.921 mg/L respectively. Meanwhile for carbonized banana peels, the concentration reduced 0.753 mg/L, 0.339 mg/L, 0.089 mg/L and 0.508 mg/L individually. It shows that the treatment using pomelo and banana peels as adsorbent has successfully reduce the concentration as the pores structure of the adsorbent could adsorbs the substances to its surface easily.